Giant adrenal myelolipoma associated with small bowel leiomyosarcoma: A case report - Eren ERSOY,; Mehmet ÖZDOĞAN,; Alp DEMİRAĞ,; Recep AKTİMUR,; Hakan KULAÇOĞLU,; Sezer KULAÇOĞLU,; Haldun GÜNDOĞDU, (Turkish Journal of Gastroenterology, 2019)
-